Kary cielesne – kontestacja a rzeczywistość - Ewa Jarosz; Cezary Kurkowski (Problemy Wczesnej Edukacji)
The paper presents two faces of the problem of corporal punishment. One is a global tendency or even a movement towards forbidding all forms of violence against children, and also those that have been traditionally presented in upbringing. There are several international legal instruments that undertake the problem of corporal punishment, starting from the Convention on the Rights of the Child. The most important ones are reviewed in the paper as well as some global initiatives that are being undertaken especially in the last decade. The other face of the problem is a practice of the everyday upbringing of children which can still be described as violent, a practice where parents still approve some violent behaviours and still behave violently towards their children. The paper presents a part of the survey carried out among parents of children below 18 years old. The results show that violence in upbringing is visible in Poland, that corporal punishment is still accepted and experienced by Polish children, although in Poland there has been an official ban of corporal punishment since 2010. The survey shows that both knowledge on the law and parents’ attitudes towards some violent behaviours should be corrected.